Individual and community level factors of malaria among under-five children in Kenya: Based on the Kenya Demographic and Health Survey - Gebeyehu Lakew; Abiyu Abadi Tareke; Zeamanuel Anteneh Yigzaw; Demis Getachew; Eyob Getachew; Amlaku Nigusie Yirsaw (PLoS ONE, 2025)
Background Malaria remains a significant global public health challenge. In Kenya, it is a leading cause of illness and death among children under five in malaria-endemic areas. Understanding its prevalence and the factors influencing it is essential for informed public health decisions and targeted interventions. Objective Assess prevalence and associated factors of malaria in under-five children using the 2022 Kenya Demographic and Health Survey data. Method A total of 3146 children were included in this study. A multilevel logistic regression model was fitted to assess factors associated with malaria, with significance reported at p-value < 0.05 and a 95% confidence interval. Results The prevalence of malaria among under-five children in Kenya was 22.72% (95% CI: 21.29, 24.22). Maternal age between 25–34 (AOR:0.75,95% CI:0.57,0.99) years, richest wealth of family (AOR 0.48, 95% CI 0.26–0.89), treated mosquito bed net (AOR = 0.39; 95% CI: 0.17, 0.89), no bed net (AOR = 0.49; 95% CI: 0.31, 0.77), mothers who are breast feeding (AOR = 0.66; 95% CI: 0.52, 0.85) and community level poverty(AOR = 1.82; 95% CI: 1.19, 2.77) were the associated factors of malaria among underfive children in Kenya. Conclusion Malaria prevalence among under-five children in Kenya was 22.72%, with risk factors including poverty and lack of bed net use, while maternal age (25–34 years), higher wealth, treated bed nets, and breastfeeding were protective. To reduce malaria, promoting the use of insecticide-treated bed nets, supporting low-income families, and strengthening maternal health education are essential. Additionally, poverty alleviation programs and enhanced malaria surveillance can help mitigate risks. Strengthening community-based interventions and improving healthcare access are crucial for long-term malaria control.